Early Clinical Experience With AZD4831, A Novel Myeloperoxidase Inhibitor, Developed for Patients With Heart Failure With Preserved Ejection Fraction. Issue 3 (2nd May 2021) - Nelander, Karin; Lagerstrom‐Fermer, Maria; Amilon, Carl; Michaëlsson, Erik; Heijer, Maria; Kjaer, Magnus; Russell, Muir; Han, David; Lindstedt, Eva‐Lotte; Whatling, Carl; Gan, Li‐Ming; Ericsson, Hans
Abstract : We evaluated safety, tolerability, pharmacokinetics (PKs), and pharmacodynamics of AZD4831, a novel oral myeloperoxidase (MPO) inhibitor, in a randomized, single‐blind, placebo‐controlled study, following once‐daily multiple ascending dosing to steady‐state in healthy subjects. Target engagement was measured as specific MPO activity in plasma following ex vivo zymosan stimulation of whole blood. Except for generalized maculopapular rash in 4 of 13 subjects receiving the 2 highest doses, 15 and 45 mg AZD4831, no clinically relevant safety and tolerability findings were observed. AZD4831 was rapidly absorbed and plasma concentrations declined slowly with an elimination half‐life of ~ 60 hours. A dose/concentration‐effect relationship between MPO inhibition vs. AZD4831 exposure was established with > 50% MPO inhibition in plasma at concentrations in the low nanomolar range. Steady‐state levels were achieved within 10 days. Taken together, the PK profile, the sustained dose/concentration‐dependent MPO inhibition, and available clinical data support further clinical development of AZD4831 in patients with heart failure with preserved ejection fraction.